2018
DOI: 10.1016/j.socscimed.2018.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Connection, meaning, and distraction: A qualitative study of video game play and mental health recovery in veterans treated for mental and/or behavioral health problems

Abstract: Rationale: Mental and behavioral health recovery includes concepts related not just to symptom improvement, but also to participating in activities that contribute to wellness and a meaningful life. Video game play can relieve stress and provide a way to connect, which may be especially important for military veterans. Objective: We examined how military veterans used video game play to further their mental and behavioral health recovery by conducting an exploratory thematic analysis of the gaming habits of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 61 publications
2
70
0
2
Order By: Relevance
“…Higher self-regulation online has been identified as a moderator between need to belong and problematic social media use in young people [ 192 ] and emotion dysregulation as a mediator between insecure attachment and addiction [ 193 ]. Although distraction is an emotion regulation strategy with a protective function against emotionally distressing states [ 111 ] and dysphoric mood [ 194 ], or is used for adaptive coping [ 195 , 196 ], deficits in attentional control, such as distraction, may also be implicated in stress, anxiety or other affective disorders [ 197 ] and in generalized anxiety disorder with core cognitive symptoms related to excessive thoughts and deficits associated with increased perseverative worry [ 198 ]. Therefore, higher mindful attention and monitoring of mood may have influenced the reduction of distraction and the enhancement of emotional control.…”
Section: Discussionmentioning
confidence: 99%
“…Higher self-regulation online has been identified as a moderator between need to belong and problematic social media use in young people [ 192 ] and emotion dysregulation as a mediator between insecure attachment and addiction [ 193 ]. Although distraction is an emotion regulation strategy with a protective function against emotionally distressing states [ 111 ] and dysphoric mood [ 194 ], or is used for adaptive coping [ 195 , 196 ], deficits in attentional control, such as distraction, may also be implicated in stress, anxiety or other affective disorders [ 197 ] and in generalized anxiety disorder with core cognitive symptoms related to excessive thoughts and deficits associated with increased perseverative worry [ 198 ]. Therefore, higher mindful attention and monitoring of mood may have influenced the reduction of distraction and the enhancement of emotional control.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some scholars argue that escapism is associated with gaming addiction and adverse emotional experiences [ 66 - 69 ]. A recent study examined the effects of video gaming on a group of military veterans with mental problems and found that video gaming contributed to their recovery by promoting individuals’ adaptive coping, eudaimonic well-being, and socializing [ 70 ]. As the evidence related to harm caused by gaming among people with schizophrenia is not yet conclusive, staff working in clinical practice need to be sensitive to and be aware of any potential harmful effects of the interventions and avoid any such threats.…”
Section: Discussionmentioning
confidence: 99%
“…Our participants regarded violent reward and violent catharsis as the least favorable motives for video gaming. Numerous studies suggest that violent games might contribute to aggression [ 70 - 72 ] and moral desensitization [ 73 , 74 ]. On the contrary, scholars also suggest that violent games support emotional coping after stressful events [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still a paucity in the literature surrounding the use and deployment of videogames by first responders/emergency services as noted by Holloway and Reger (2013), who have constructed a purpose-built environment in Second Life to educate various actors in the various issues and factors surrounding PTSD. The field of Games for Health has embraced the design, use, and development of videogames/environments for multiple health conditions, (Colder et al, 2018;Macleod and Sloan, 2017;Callejas-Cuervo et al, 2017;Holloway and Reger (2013). Yet, there is very little research indeed that has explored the use of mHelath Apps, videogames, and virtual environments to support and combat PTSD and related issues by police personnel and emergency responders.…”
Section: Discussionmentioning
confidence: 99%